DESIGN OF BUSINESS PROCESS IMPROVEMENT FOR THE AMBULANCE AND HUMANITARIAN SERVICES DIVISION AT RUMAH AMAL SALMAN - Dwi Permatasari, Intan
A business process is a set of business activities which aims to carry out the objectives in producing a product or service within a company or organization. Business processes are applied to control the running of business activities and facilitate the employees to carry out activities according to predetermined procedures. In this study, the Ambulance and Human Services Division at the Salman Charity House did not yet have a fixed business process, which caused an increased work and ineffective business activities. This study aims to design business process improvement proposals by modeling and evaluating existing business processes so that they can run more effectively and efficiently. The business process improvement (BPI) framework is used for identifying the institution's business processes. Furthermore, a risk assessment is performed using the failure mode, effect, and criticality analysis (FMECA) method. The results of the risk analysis will be written into the fishbone analysis to make improvements to the resulting risks. In addition, value-added assessments are carried out to assess business process performance, reduce waste, and provide value for more profitable business processes. The results of the value-added assessment will become input in designing risk improvements and streamlining business processes. Through risk assessment analysis using the FMECA method, seven business processes with priority risks that need to be improved are identified. In addition, the results obtained from the evaluation of existing business processes with a value-added assessment show that 22 business processes, or 29.7%, are classified as non-valueadded (NVA), 34 business processes, or 45.9%, are classified as organizational valueadded (OVA), and 18 business processes, or 24.3%, are classified as real value-added (RVA). The proposed business process improvements designed in this study are in the form of two proposed improvement documents developed through a project charter to correct risks that may occur in business processes and streamline business processes.